Cesarean scar pregnancy: Case report and review of the literature - Andraž Dovnik; Polona Kores Testen; Lea Mlakar; Milan Reljič; Darja Arko; Iztok Takač (Acta Medico-Biotechnica, 2021)
Purpose: A cesarean scar pregnancy is a rare form of ectopic pregnancy in which the gestational sac is implanted in the uterine scar after a previous cesarean section. Early diagnosis is crucial, and transvaginal ultrasound is the most appropriate diagnostic tool. Different management options have been described in the literature; however, there is no consensus regarding optimal treatment due to the rarity of the condition.Case report: We present a case involving a cesarean scar pregnancy which was managed with hysterotomy due to the advanced stage of pregnancy (fetal crown–rump length = 3.5 cm).Conclusion: Early diagnosis of a cesarean scar pregnancy is important to avoid complications and to preserve fertility. Various treatment modalities have been described in the literature, including medical and surgical options.